Influence of Thickness of Active Silicon Nanoparticle Films in Heterojunction Photodetectors. Issue 12 (6th May 2022) - Charumathi, Nataraj; Dey, Sukumar; Mohanta, Kallol
Abstract : Indirect bandgap in Si‐based semiconductor limits its widespread usage as the main component for effective sunlight harvesting and led to the development of new silicon structures with small direct bandgaps and desired optical properties. Herein, the synthesis of quasi‐direct bandgap silicon nanoparticles (SiNP) by a one‐pot hydrothermal process and their application as an active layer of photodetectors are reported. The result shows that these photodetectors are operable over a long range of wavelengths and can respond in just 0.4 ms. Systematic characterizations of multiple devices led to determining the critical thickness of the silicon nanoparticles (SiNPs) active layer in photodetectors for its optimum response. The reliability, repeatability, and range of operation of an optimized device have been evaluated. This work suggests the usability of SiNP for the development of photodetectors and the significance of the thickness of the SiNP active layer in the further fabrication of optoelectronic devices. Abstract : The work focuses on the fabrication of photodetector devices with quasi‐direct bandgap silicon nanoparticle (SiNP) as an active component. To find out the optimized responsivity in photodetector devices, the layer thickness of silicon nanoparticles has been varied. This extensive study on thickness of SiNP layers could open up possibilities for the fabrication of silicon‐based fast photodetectors.